STRATEGI EFEKTIF DALAM PEMENUHAN KEBUTUHAN SUMBER DAYA MANUSIA DI UNIT PENDIDIKAN, PELATIHAN, DAN PENELITIAN (DIKLATLIT) RUMAH SAKIT ADVENT BANDAR LAMPUNG MELALUI RE-DISTRIBUSI DAN TRAINER INTERNAL - Lestari, Rizky Aprilianti; Mayasari, Fitri Yuli; Ahmad Mukhtaruddin Syarfan; Elyana Afifa Afra; Oktapianingtyas, Aulia Rahma; Azizah, Fatikha Syiam; Sihab, Najwa; Pustika, Fita; Andin Pinesti Suryaning Sarah (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction: Meeting human resource (HR) needs in hospitals is a significant challenge in providing optimal healthcare services. The Education, Training, and Research (Diklatlit) Unit plays a strategic role in HR development. The importance of qualified human resources in improving service quality and hospital competitiveness is undeniable. Effective and efficient healthcare services depend heavily on the skills, knowledge, and professional attitudes of both medical and non-medical personnel. Methods: This research was conducted through Field Learning Experience (PBL) activities using an observational and participatory approach at Adventist Hospital Bandar Lampung. The research method was carried out in several ways, namely: 1) Direct observation of activities and work processes in the Training and Development Unit and related units in the hospital, 2) Semi-structured interviews with the head of the Training and Development Unit, 3) Documentation of training policies, training schedules, and results of previous training evaluations. Results: The main problems were a shortage of HR and excessive workload in the Diklatlit Unit. The HR redistribution strategy and the development of internal trainers were identified as effective solutions in supporting the sustainability of the training program. Conclusion: The implementation of HR redistribution and internal training has been proven to support the efficiency and sustainable capacity building of the Diklatlit Unit.